Solve the equation 5cos^2x-6tanx*cosx=cos^2x-5sin^2x-1.
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
We have to solve 5(cos x)^2 - 6 tan x*cos x = (cos x)^2- 5*( sin x)^2 - 1
5(cos x)^2 - 6 tan x*cos x = (cos x)^2- 5*( sin x)^2 - 1
=> 5(cos x)^2 + 5*( sin x)^2 - 6 tan x*cos x = (cos x)^2 -...
(The entire section contains 131 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- Prove the following identity: cos x + cos 2x + cos 3x = cos 2x(1 + 2cos x)
- 1 Educator Answer
- What is x if cos^2(x/2)-2cos^2x=(3/2)*square root2(1+cosx)+2sin^2x?
- 1 Educator Answer
- Prove the identity cotx*sinx=cosx/(cos^2x+sin^2x)
- 1 Educator Answer
- Solve the equation tan^2x=8-8secx.
- 1 Educator Answer
- What is the angle x if the identity sin2x-(cos 2x)/2 -1/2=cosx-2cosx*tanx?
- 1 Educator Answer
For the beginning, we'll move all terms to one side:
5(cos x)^2 - 6tanx*cosx - (cos x)^2 + 5(sin x)^2 + 1 = 0
We'll re-group the terms:
[1 - (cos x)^2] - 6tanx*cosx + 5[(sin x)^2 + (cos x)^2] = 0
We'll write the fundamental formula of trigonometry;
[(sin x)^2 + (cos x)^2] = 1
(sin x)^2 = 1 - (cos x)^2
We also know that tan x = sin x/cos x
The equation will become:
(sin x)^2 - 6sinx*cos x/cosx + 5 = 0
We'll simplify and we'll get:
(sin x)^2 - 6sinx + 5 = 0
We'll substitute sin x = t
t^2 - 6t + 5 = 0
We'll apply quadratic formula:
t1 = [6 + sqrt(36 - 20)]/2
t1 = (6+4)/2
t1 = 5
t2 = (6-4)/2
t2 = 1
But sin x = t
sin x = t1
sin x = 5, impossible since sin x =< 1.
sin x = t2
sin x = 1
x = k*arcsin 1 + kpi
x = k*pi/2 + kpi
The solution of the equation is: {k*pi/2 + kpi}.
Student Answers